Factors Effecting English Speaking Ability of Second Year Students in the Faculty of Humanities and Education, Mahamakut Buddhist University - Wankong, Anchanida (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The objectives of this research study factors effecting English speaking ability of second year students in the Faculty of Humanities and Education, Mahamkut Buddhist University. The study sampling subjects were 40 second year students who are studying in first semester 2016 at Mahamakut Buddhist University. The sampling was chosen from 2 faculties are Humanities Faculty and Education Faculty.The instrument used for data collection was questionnaire. Data were analyzed for percentage, mean, and standard deviation. The findings of the study indicate that the second year students from 2 faculties namely: Humanities faculty and Education faculty in first semester 2016 at Mahamakut Buddhist University thought factors effecting English speaking ability of second year students in the Faculty of Humanities and Education, Mahamkut Buddhist University at a high level. When considering by aspect, it was found that the highest mean was learning behavior, student’s personality, student’s attitude toward learning, basic experience in studying English, and promoting and supporting the learning of the family.